Comparative analysis of body composition in youth elite football players: Insights from professional academies - Ivanov, Danail (Universitas Tanjungpura, 2025)
Background and Study Aim. Body composition plays an important role in determining athletic performance in soccer. Optimal levels of muscle mass and body fat percentage are key factors that influence speed, endurance, strength and overall physical readiness. Understanding and monitoring these parameters is crucial for player development, allowing coaches to design effective training programs tailored to their individual needs.Material and Methods. This study examined the body composition profiles of 66 football players from the academy of PFC Levski Sofia, categorized into four age groups: U15, U16, U17, and second team. Measurements were taken using the InBody 230 bioelectrical impedance analyzer, which assesses key metrics such as skeletal muscle mass, body fat percentage, BMI and fat-free mass. To identify significant age-related trends, advanced statistical methods were used, including descriptive analysis, ANOVA, and regression analysis.Results. The ANOVA results validated these findings, by showing statistically significant differences between age groups (F-statistic = 1199.91, p < 0.05). These results confirmed that anthropometric indices, including weight, height, BMI, and body fat percentage, varied significantly across different age categories, highlighting the importance of customized training and nutrition strategies at each stage of development. The findings revealed a consistent increase in body weight, height and BMI with age, accompanied by a significant decrease in body fat percentage. These trends are in line with existing literature, which reinforces the importance of body composition monitoring as part of player development.Conclusions. This study underscores the importance of body composition monitoring in optimizing performance, preventing injury, and guiding individualized training programs for elite youth soccer players. Customized training and nutrition strategies are essential to ensure optimal physical development and long-term success in competitive soccer.